2013
DOI: 10.1371/journal.pone.0068426
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Cytokines and Other Inflammatory Markers for the Early Diagnosis of Neonatal Sepsis–A Case Control Study

Abstract: ObjectiveCytokines (IL-6, IL-8 and TNF-α), sCD163, and C-reactive protein were serially measured in an attempt to identify a set of tests which can reliably confirm or refute the diagnosis of neonatal sepsis at an early stage.MethodsOne hundred neonates suspected to have sepsis on clinical grounds and who met the inclusion criteria were enrolled for the study. Based on the positive or negative blood culture reports they were classified as infected (n = 50) and non-infected (n = 50) neonates respectively. Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 24 publications
2
57
0
2
Order By: Relevance
“…6,8,14,15 A study by Smulian et al, reported that IL-6 level showed a highly significant value even in umbilical cord blood in septic neonates. 16 Another study done by Buck et al, also showed similar sensitivity in culture positive and clinical sepsis neonates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,8,14,15 A study by Smulian et al, reported that IL-6 level showed a highly significant value even in umbilical cord blood in septic neonates. 16 Another study done by Buck et al, also showed similar sensitivity in culture positive and clinical sepsis neonates.…”
Section: Discussionmentioning
confidence: 99%
“…8 The blood culture is the gold standard for the diagnosis although it is time consuming and it may be negative due to inadequate sample collection or administration of antibiotics intrapartum or intermittent. 5 However, in this study we have taken only the neonates who were blood culture positive to study the cytokine IL-6 and the most commonly used acute phase reactant CRP or hs-CRP or ESR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD64 receptor on neutrophils is a Fcγ receptor 1 for immunoglobulines G (IgG) and has been found to be one of the most useful markers for diagnosis of infection or sepsis beside common CRP and PCT [17][18][19][20][21]. CD64 expression in patients with sepsis is normally induced within two to four hours.…”
Section: Introductionmentioning
confidence: 99%
“…Term and near-term neonates were diagnosed with suspected clinical sepsis based on a Töllner score of ≥10 or a Töllner score of 5-10 but with the presence of one or more of the following factors associated with an increased risk of infection: maternal fever (≥38°C), prolonged rupture of membranes >18 h and clinical chorioamnionitis [9,19,20]. Inclusion criteria were positive clinical signs of sepsis and/or a history of factors associated with a raised risk of infection.…”
Section: Early-onset Neonatal Sepsis Groupmentioning
confidence: 99%